Iran in the early Islamic period : politics, culture, administration and public life between the Arab and the Seljuk conquests, 633-1055 - Spuler, Bertold, 1911- (Iran Studies, 2015)
This book presents a translation of Bertold Spuler's groundbreaking work on the transformation of Iran from a Persian Zoroastrian Empire to a province of the Arab Muslim Empire to a land divided by a number of Persian and Turkish kingdoms.